Incorporation of Matrix Form in Time-Varying Finite Memory Structure Filter - Soo Kim, Pyung; ., . (International Journal of Engineering and Technology, 2018)
This paper develops a computationally efficient algorithm for the time-varying finite memory filter with matrix form under a weighted least square criterion using only finite observations on the most recent window. Firstly, the time-varying finite memory filter is represented in matrix form as an alternative of recursive form. Secondly, a computationally efficient algorithm is derived to obtain the numerical stability for improving computational reliability and the amenability for the parallel and systolic implementation, which can reduce computational burden. The computationally efficient algorithm is derived from the recursive form of time-varying finite memory filter by applying a square-root strategy. Through computer simulations for a sinusoid signal and diverse window lengths, the proposed algorithm can be shown to be better than the infinite memory filtering based algorithm for the temporarily uncertain system. Â Â